Results of Screening for Psychiatric Residents in Psychiatric Risk Groups - Naewman, Somboon (Journal of Health Science of Thailand, 2019)
The purpose of this study was to investigate the outcomes of psychiatric screening in the risk population in order to identified people with psychiatric disorders and provide appropriate treament and care. It was conducted as a descriptive study in Khokhom area, Uthumphon Phisai District, Srisaket Province from October 2015 to September 2016. Data collection was performed by using a psychiatic screening test; and the screening process was conducted by performed by interviewing 160 vulnerable individuals in the communities who had signs or symptoms in line with the psychiatric risk criteria. Data were analyzed by using percentage, mean and standard deviation. It was found that most of the risk population were male (56.2%). The age range was 40-49 years (35.0%). The average age was 46.83 years old and the lowest was 19 years old, and the oldest age was 70 years old. Most of the samples were members of family (87.5%). The majority of them were married (86.5%); and the level of education was at the elementary level (95.0%). Majority of them were agricultural workers (93.8%). Psychiatric disorder was detected in 10 respondents; and the most common symptoms were alcohol or substance abuse (6 persons or 60.0% of the cases). There were 10 patients who had speech and hearing abnormality. All cases were referred to get medical attention for proper diagnosis and treatment. Eight of them were diagnosed as psychiatric patients and treated; and the rest (2 cases) were monitored and assessed on a continuous basis.